INNOVATION IN THE AGRICULTURAL SECTOR OF UZBEKISTAN: REALITIES AND PROSPECTS FOR PRODUCTION OF ORGANIC COTTON - Karamatov, O. O.; Khaldarov, A. D.; Rakhmanov, Sh. K. (Tadqiqot, 2020)
The demand for textile products which are produced on organic cotton has been increasing every year. Therefore, the countries producing organic cotton are annually increasing the volume of its production. Uzbekistan, although it is one of the main producers and exporters of cotton in the world market, has been producing organic cotton only since 2019. The country has all facilities for the further development of organic cotton production, since in recent years, in order to gradually liberalize the agricultural sector, radical changes have taken place, especially in cotton growing. The adopted legal acts have contributed to improving the organization of agrarian and processing industries; new structures have been organized, uniting the whole cycle of cotton production, processing and marketing of textile products through agricultural clusters. The study claims that the main producers of organic cotton and textile products may be cotton-textile agro clusters, which have the opportunity to independently enter the world market and cover a certain segment of the organic cotton market. This study is aimed at studying the experience and analysis of the production of organic cotton in the agricultural cluster Textile Technologies Group LLC. It assesses the development opportunities for organic cotton production in the republic.
Keywords: 2. Zero hunger; 9. Industry and infrastructure